2021
DOI: 10.1371/journal.pone.0250444
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of undergraduate student knowledge, attitude, and practices towards COVID-19 in Debre Berhan University, Ethiopia

Abstract: Background Novel coronavirus-2019 (COVID-19) is a highly infectious disease that has caused a global pandemic. As of July 2020, there were 8,475 confirmed cases of COVID-19 in Ethiopia, and a total of 52 cases and 1 death were reported in Debre Berhan where this study was conducted. Under these conditions, we sought to assess what undergraduate students at Debre Berhan University knew about COVID-19 and how it shaped their attitudes and practices regarding this disease. Objective The aim of the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
(48 reference statements)
7
17
3
2
Order By: Relevance
“…Online information becomes one of the principal and rapid ways to obtain information, compared with other resources [ 23 ]. The result of this study are consistent with those studies conducted in Egypt [ 30 ] and Ethiopia [ 26 ] that reported internet and social media as a main source of information. Against other media, newspaper, religious and community leaders, and heath extension workers appears to be a less favored option for gathering knowledge about the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Online information becomes one of the principal and rapid ways to obtain information, compared with other resources [ 23 ]. The result of this study are consistent with those studies conducted in Egypt [ 30 ] and Ethiopia [ 26 ] that reported internet and social media as a main source of information. Against other media, newspaper, religious and community leaders, and heath extension workers appears to be a less favored option for gathering knowledge about the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The good knowledge of students towards COVID-19 in this study might be due to the late confirmed case report of COVID-19 in Ethiopia, which might provide adequate time to know about the disease. Besides, the WHO declaration of the disease as a pandemic might also have increased the students’ knowledge [ 26 , 27 ]. Effective education by the WHO and the Ethiopian government and also active information seeking of students about COVID-19 from various channels of information and the official website of the Ministry of health of Ethiopia might contribute to good knowledge of students about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this meta-analysis showed that the pooled proportion of college students’ knowledge of COVID-19 was 74%, which is similar to the findings reported by Aynalem YA et al [ 59 ]. The results of subgroup analysis showed that the pooled proportion of Chinese college students’ mastery of COVID-19-related knowledge had gradually increased over time, and female and medical college students had a higher level of knowledge towards COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…Only 97 (26.2%), 121 (32.7%), and 108 (29.2%) of students had good practice regarding physical distance, frequent hand washing, and facemask use respectively. These results are lower than the findings reported by different previous studies [ 15 , 16 , 26 , 29 ]. The discrepancy may be explained by the fact that previous studies were conducted at the beginning of the introduction of COVID-19 when everybody was scared and had taken preventive measures aggressively.…”
Section: Discussioncontrasting
confidence: 85%
“…For example, 74.5% of students wear a facemask and 85% of students washed their hands frequently in Bangladesh [ 12 ], 80.0% of students adopted social isolation strategies, regular hand washing, and enhanced personal hygiene measures in Jordan [ 13 ] and more than 94% of students were following the recommended preventive health behaviors in Iran [ 14 ]. On the other hand, few studies among Ethiopian university students have shown unsatisfactory compliance behavior of students towards COVID 19 preventive measures, where only 56% of students keep their physical distance, 74% wash their hands frequently [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%